Enhancing Conservation Efforts of Stephanopodium engleri Through Vegetative Propagation: Effects of IBA and Cutting Types - Giselly Mota da Silva; Evandro Alves Vieira; Luiz Palhares Neto; Silvio Ramos; Markus Gastauer; Cecílio Frois Caldeira (Plants)
Stephanopodium engleri Baill. is an endangered tree species from the Dichapetalaceae family and endemic to the Iron Quadrangle region of Brazil. Recalcitrance and low seed viability limit conventional seedling production, making vegetative propagation a crucial alternative for conservation efforts. This study evaluated the rooting and sprouting potential of different cutting types (apical, middle, and basal segments from the main stem, as well as the tip and the herbaceous and woody segments from the lateral branches) treated with Indole-3-Butyric Acid (IBA) at varying concentrations (0, 1, 2, 3, and 4 g L−1) and immersion durations (5 s to 10 min). Cuttings were collected from 12-month-old plants grown under controlled conditions and planted in Carolina Soil® substrate after treatment. Sprouting and rooting rates varied significantly between cutting types, with basal main stem cuttings showing the highest rooting success, particularly at 3 g L−1 of IBA. These cuttings also exhibited more and longer roots and enhanced sprouting-related biometric traits. Shorter immersion times (15 s and 1 min) were the most effective, promoting root formation while avoiding the potential inhibitory effects of prolonged exposure. Our findings provide a practical protocol for large-scale seedling production of S. engleri while minimizing impacts on wild populations. The effective use of vegetative propagation could facilitate the expansion of S. engleri populations in their natural habitats, enhancing conservation efforts and ensuring sustainable species management.